Analysis of The Covid-19 Impact on Electricity Consumption and Production - Mehmet Bulut (Sakarya University Journal of Computer and Information Sciences, 2020)
With the year 2020, the world faced a new threat that affects all areas of life, negatively affects production in all areas and paralyzes social life. The measures and restrictions taken by the country's governments to prevent the epidemic from spreading rapidly in the society with the effect of the coronavirus (Covid-19), which first appeared in China and spread all over the world, brought a new lifestyle. Covid-19 has been much the impact on electricity use and electricity production in the period in Turkey as like other countries. There was a sharp decline in commercial and industrial electricity use. The coronavirus effect has also been reflected in the electricity demand and the consumption amount has undergone a great negative change. Due to the enactment of measures against the new type of coronavirus epidemic and the partial or full-time curfews, electricity consumption was moved to homes, supermarkets and hospitals in April 2020 from places where mass consumption is intense, such as industry, workplaces and educational institutions. In this study, Covid-19 period, the first cases were examined electricity production and consumption in Turkey as of the date it is seen throughout, in comparison with electricity consumption data in the same month of the previous years corresponding to this period, the effects on electricity generation and consumption habits of this period were examined.